Introduction. Normes, silences, pouvoirs : pour une anthropologie critique des “violences fondées sur le genre” - Giovanna Cavatorta (Archivio Antropologico Mediterraneo)
This article outlines some reflections towards a critical anthropology of gender-based violence, which is interpreted as an object of politics, even a governmental stake, where moral economies and specific forms of victimization and culturalization emerge. The text introduces and discusses the papers that have been presented during a seminar held at the Centre Norbert Elias of Marseille in 2019. In this occasion, by a feminist perspective and through a diversity of fieldwork and approaches, the participants analyzed the dynamics of power that distinguish the definition, the denunciation, the speaking out and the silencing of this violence. Thus, this article explores the advantages of questioning, through the ethnography, the processes that qualify as intolerable some practices about gender and the ways in which the speaking out is allowed and hierarchized by norms and institutions.